The relationship between emotional intelligence and extrinsic career success among employees in a case of Dewan Undangan Negeri Sarawak / Hanis Ahmad Zaki Mohd Zulkipli - Mohd Zulkipli, Hanis Ahmad Zaki (2017)
This research has been done by the researcher in order to find out the relationship between emotional intelligence and extrinsic career success among the public sector employees. The main objective of this study is to find out the relationship between emotional intelligence and extrinsic career success. The involvement of the employees in Dewan Undangan Negeri for this study was 30 staff. In order to collect data, the researcher use questionnaire and distribute it to all 30 staff in Dewan Undangan Negeri. Unfortunately, 29 out of 30 questionnaires was able to retrieved by the researcher. The reliability test for this study was done using SPSS Statistics version 20. The result shows that there is negative relationship between emotional perception (r= -0.023), emotional facilitation (r== -0.469) and emotional management (r=-0.646) with extrinsic career success. However, the relationship between emotional understanding (r= 0.079) and extrinsic career success was positive. It is advisable for the future researcher should choose the best and easy topic to look for data and expand their number of respondent in order to get valid and accurate result.